Metformin during Pregnancy: Effects on Offspring Development and Metabolic Function - Jorquera, Gonzalo; Echiburú, Bárbara; Crisosto, Nicolás; Sotomayor-Zárate, Ramón; Maliqueo, Manuel; Cruz, Gonzalo (Frontiers in Pharmacology, 2020)
Maternal obesity during pregnancy and Gestational Diabetes Mellitus are both associated to several postnatal impairments in offspring, including obesity, early origin hypertension, Diabetes Mellitus, and reproductive alterations as well. Metformin is an oral euglycemic drug whose use is being evaluated to treat Gestational Diabetes Mellitus, insulin resistance associated to obesity and Polycystic Ovary Syndrome during pregnancy. The beneficial effects of metformin on glycemia and pregnancy outcomes place it as a good alternative for its use during pregnancy. Although some rationale indicates that improving the metabolic status of the pregnant mother by using metformin should avoid the consequences of insulin resistance on the offspring fetal and postnatal development, some human and animal studies have indicated that metformin during pregnancy could amplified these alterations and be associated with postnatal weight gain excess and obesity. In this minireview we discuss the clinical and experimental evidence which support the benefits of using metformin during pregnancy but also discuss the evidence showing a possible negative impact of the drug on offspring development.